Resilient seed systems: Handbook. Second edition - Vernooy, Ronnie; Bessette, Guy; Otieno, G. (Bioversity International, 2019)
The Resilient Seed Systems Handbook Second Edition, developed by a multidisciplinary team of Bioversity International researchers and research partners, is a tool that supports research and capacity building on resilient seed systems in the context of adaptation to climate change. The first edition (Resource Box for Resilient Seed Systems: Handbook) was published in 2016. The modules of the handbook represent steps of a participatory research cycle from situational analysis to knowledge sharing and communication. This second edition includes a new module on seed production and distribution and incorporates several of more recent useful ideas, examples of good practices and the latest references.